Scaling analysis of the hydraulic behavior in reactor pressure vessel. (15th December 2021) - Wang, L.S.; Yan, B.H.
Highlights: A scaling analysis for the hydraulic behavior in reactor pressure vessel is conducted. Scaling criteria for the reactor hydraulic test are obtained. Important phenomena with high ranking in the hydraulic test are analyzed. Some valuable suggestions for the future test are listed. Abstract: The hydraulic behavior of coolant flow in reactor pressure vessel plays an important role in the thermal hydraulic and safety analysis of nuclear reactor system. Conventional reactor hydraulic tests were carried out by linearly down scaled facilities without tough physical principle. In this work, a scaling analysis in control volume scale for the hydraulic behavior in reactor pressure vessel is conducted to develop a theoretical basis for the down scaled hydraulic test. The mass, axial and lateral momentum conservation in reactor core is analyzed. Important scaling criteria for the reactor hydraulic test are obtained. It is found that the flow velocity should be reduced to promise the similarity of all scaling criteria. The identical velocity simulation with linear scaling method could results a distortion of about 16% to the lateral mixing criterion. This work is helpful to establish the theoretical basis for the hydraulic experiment and numerical research.